Durian Seed Starch and Rind Liquid Smoke-Based Edible Coating for Apple Preservation - Faisal Muhammad; Fauzi; Abubakar Yusya; Mukhlishien; Desvita Hera; Sovianti Meilan; Tantri Siregar Kalyana (BIO Web of Conferences, 2025)
This study explores the use of an edible coating from durian seed starch combined with liquid smoke derived from durian rind waste for apple preservation. The liquid smoke was prepared through the pyrolysis at three different temperatures: 340°C (T1), 380°C (T2), and 420°C (T3). The edible coatings were formulated by mixing the liquid smoke at concentrations of 2% (C1), 4% (C2), and 6% (C3) with durian seed starch and chitosan. The characteristics of the edible coatings were examined using Fourier Transform Infrared (FTIR) Spectroscopy and X-ray Fluorescence (XRF). Antibacterial properties were tested against Escherichia coli and Staphylococcus aureus. Additionally, physical and sensory evaluations, including thickness measurement, organoleptic tests, Total Plate Count (TPC), and colorimetric analysis, were conducted to assess the coatings’ effectiveness in extending the shelf life of apples. The test results suggest that edible coatings T1C1, T2C2, and T3C3 had good features and met with the Indonesian national standards. The FTIR results identified the optimal edible coating as the combination T3C3, which exhibited significant antibacterial activity, with inhibition zones measuring 14.66 mm for E. coli and 6.07 mm for S. aureus. The T3C3 coating demonstrated a thickness of 0.031 ± 0.01 mm when applied to apples. After 25 days of storage, the TPC value was 8.1×104 CFU/g, indicating that the apples remained within acceptable quality standards. Organoleptic assessments revealed that the T3C3-coated apples maintained their texture, firmness, and aroma for more than 20 days.